Persepsi Pelanggan Terhadap Kualitas Pelayanan Wedding Organizer “By Your Side” Jimbaran, Bali - Lidya Lidya; I ketut Arjaya; Indah Kusumarini (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
This study aims to determine the service quality of By Your Side (BYS) wedding organizers. BYS, which has been established since 2016, has handled 100 weddings until 2021. Of the many wedding activities it has handled, there have been a number of complaints from customers about the quality of BYS's service. Such as venue convenience, complaint handling, access, poor communication and implementation of wedding activities. To determine the quality of BYS services, the theory of service quality dimensions from Parasuraman, Zeithaml, Berry (2011) is used. Judging from the five dimensions, namely physical evidence (tangible), reliability (reliability), responsiveness (responsiveness), assurance (assurance), and caring (empathy). The results showed that the average value of BY's service quality was 4.09 (Good). On the tangible dimension, a value of 4.37 was found, the reliability dimension; 4.34, responsiveness; 3.87, assurance dimension; 3.39 and the empathy dimension; 4.48. Of the five dimensions, it can be seen that the highest score is on the empathy dimension, while the lowest score is on the assurance dimension. Therefore, the assurance dimension needs more attention. Such as providing training to By Your Side employees to better understand what products the company has, creating a sense of security and comfort for consumers.